2008
DOI: 10.1128/jcm.00777-08
|View full text |Cite|
|
Sign up to set email alerts
|

Extended-Spectrum Beta-Lactamase Detection with Different Panels for Automated Susceptibility Testing and with a Chromogenic Medium

Abstract: Infections caused by extended-spectrum beta-lactamase (ESBL)-and ampC beta-lactamase-producing gramnegative bacteria complicate therapy and limit treatment options. Several different panels for ESBL detection with automated systems exist. In addition, a chromogenic agar medium is available for ESBL screening. We compared two automated identification and susceptibility testing systems with regard to their effectiveness in detecting ESBL production in Enterobacteriaceae: the BD Phoenix system (BD Diagnostic Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
3
22
0
3
Order By: Relevance
“…In this study, we decided not to increase the incubation time beyond 24 h based on previous studies, which all indicated little gain in ESBL recovery rates but rather an increase in interfering growth of associated flora (7,8,17).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we decided not to increase the incubation time beyond 24 h based on previous studies, which all indicated little gain in ESBL recovery rates but rather an increase in interfering growth of associated flora (7,8,17).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these utilized strains expressing commonly occurring TEM-, SHV-, and CTX-M-type ESBLs, although successful recovery of enterobacterial strains harboring ESBLs isolated less frequently (VEB, GES, BEL, PER, TLA-1, TLA-2, BES, and OXA-18) has also been demonstrated on chromID ESBL (22). However, the specificities observed for this medium have been very low (11% to 44%) due to growth of AmpC-overproducing organisms (8,10,16,21). A drastic decrease in specificity (44%) of chromID ESBL was observed when strains with chromosomal AmpC ␤-lactamases were tested compared to the high specificity (94%) of this medium while evaluating non-AmpC-producing Enterobacteriaceae (Table 1) (16).…”
Section: Culture-based Detection Of Esbl-harboring Enterobacteriaceaementioning
confidence: 99%
“…Evaluation studies of ESBL chromogenic media using well-characterized strains are summarized in Table 1. Most studies comparing the performance of chromID ESBL to selective media, automated tests, or other chromogenic media have shown almost uniformly high sensitivities (Ͼ95%) of this medium (8,10,16,21,22). The majority of these utilized strains expressing commonly occurring TEM-, SHV-, and CTX-M-type ESBLs, although successful recovery of enterobacterial strains harboring ESBLs isolated less frequently (VEB, GES, BEL, PER, TLA-1, TLA-2, BES, and OXA-18) has also been demonstrated on chromID ESBL (22).…”
Section: Culture-based Detection Of Esbl-harboring Enterobacteriaceaementioning
confidence: 99%
“…En China, con tradición de consumo de alimentos crudos, existe una normativa de calidad que incluye recuento de mesófilos, identificación de organismos indicadores de higiene, e identificación específica de patógenos transmitidos por alimentos. 4 En Brasil existe una normativa de calidad para kibbeh crudo. 5 Estos hallazgos pueden sustentar la revisión de criterios de calidad para el consumo de preparaciones crudas y contribuir a prevenir y monitorear las ETA con el fin de avanzar en la planificación de la vigilancia epidemiológica en nuestros países.…”
unclassified